Integrated citizen centered digital health and social care : citizens as data producers and service co-creators ; proceedings of the EFMI 2020 Special Topic Conference - Värri, Alpo (Studies in health technology and informatics, 2020)
"As citizens, we must all take responsibility for our own health to some extent, and recent developments in medical informatics have provided some valuable new ways to help us do that.This book presents the proceedings of the 2020 Special Topic Conference of the European Federation for Medical Informatics (EFMI STC 2020), held for the first time as a virtual conference on 26 & 27 November 2020, due to restrictions associated with the COVID-19 pandemic.Entitled Integrated citizen centered digital health and social care - Citizens as data producers and service co-creators, this conference focused on the citizen-centered aspects of health informatics. This topic provided the opportunity for contributors to present innovative solutions to allow citizens to take greater responsibility for their health with the help of information and communication technology, and the 52 presented papers published here cover a wide range of areas under the broad, invited subject headings of: tools and technologies to support citizen-centered digital services; capacity building to enhance the development and use of digital services; confidentiality, data integrity and data protection to guarantee trustworthy services; citizen safety in digital services; effectiveness and impact of citizen-digital and integrated health and social services; evaluation approaches and methods for digital services; usability, usefulness and user acceptance of digital services; and guidelines for the successful implementation of digital services for citizens.Offering a current overview of research and applications, the book will be of interest to all those health professionals working to increase citizen use of digital healthcare"--